2022
DOI: 10.1177/00315125221090203
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Baby Swimming on Motor and Cognitive Development: A Pilot Trial

Abstract: Contact with water, even from birth, may be an important experience for child development. In this work, we aimed to investigate if baby swimming might influence infant development in motor and cognitive domains. We assigned infants to either a 10-week baby swimming intervention ( n = 12; M age = 13 months ( SD) = 7) or a control group ( n = 15; M age = 22 months ( SD) = 6). We assessed motor development with the Peabody Developmental Motor Scales (2nd edition, PDMS-2) and cognitive development with core tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 61 publications
(88 reference statements)
1
12
0
1
Order By: Relevance
“…One pilot study [ 39 ] pointed to an increase in developmental percentile (measured using AIMS) after baby swimming program intervention. Similar results were found in cross-sectional studies showing significant improvements in gross [ 40 , 41 , 43 ], fine, and total motor development [ 41 ] in infants participating in swimming programs when compared with the control groups and that four-year-old children who previously participated in baby swimming programs had better scores in prehension (ball skills) and in static balance (one-leg balance) than children that did not participate in baby swimming programs [ 38 ]. In cognitive performance, no significant pre- or post-test differences were found in either the intervention or control group, only a marginal tendency towards intervention-related gains in inhibition speed and response selection (or shifting) accuracy [ 41 ].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…One pilot study [ 39 ] pointed to an increase in developmental percentile (measured using AIMS) after baby swimming program intervention. Similar results were found in cross-sectional studies showing significant improvements in gross [ 40 , 41 , 43 ], fine, and total motor development [ 41 ] in infants participating in swimming programs when compared with the control groups and that four-year-old children who previously participated in baby swimming programs had better scores in prehension (ball skills) and in static balance (one-leg balance) than children that did not participate in baby swimming programs [ 38 ]. In cognitive performance, no significant pre- or post-test differences were found in either the intervention or control group, only a marginal tendency towards intervention-related gains in inhibition speed and response selection (or shifting) accuracy [ 41 ].…”
Section: Resultssupporting
confidence: 89%
“…The positive effect on child neurodevelopment reported by Garcia and colleagues in their systematic review [ 17 ] was confirmed for infants younger than 36 months in the present review. Although three studies had already been included in Garcia et al’s review [ 38 , 39 , 48 ], more recent studies confirmed the positive effects of aquatic activities exposure on infants’ development [ 41 , 42 , 43 , 49 ]. Baby swimming programs were associated with improvements in gross, fine, and total motor development [ 39 , 40 , 41 , 43 ] (even when the children are older [ 38 ]); improvement in motion perception [ 42 ]; and a tendency for an improvement in early executive function skills [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perkembangan psikomotorik anak berusaha untuk membekali anak dengan keterampilan yang diperlukan untuk menjamin prestasi sekolah yang baik (Hudson & Willoughby, 2021). Keterampilan motorik dasar seperti melompat atau berlari berkorelasi dengan pencapaian kognitif di berbagai bidang seperti bahasa Inggris, matematika, olahraga, dan teknologi (Borioni et al, 2022;Sofyan et al, 2022). Aktivitas fisik terkait usia dan mampu meningkatkan fungsi kognitif (Gerten et al, 2022).…”
Section: Pendahuluanunclassified
“…The first article in this series is a rare, provocative effort to influence infants’ EF through parent-infant swim training. Federica Borioni and her colleagues (2022) provided clear evidence that swim training in parent/baby pairings benefitted babies’ gross and fine motor development; they also offered preliminary but more equivocal suggestions of cognitive benefits for babies from this training. While EF is primarily mediated by frontal lobes of the brain and can only be reliably measured from late childhood, concomitant with rapid growth in the frontal lobes (Anderson, 2002), these authors applied creative cognitive measurement tools that suggest possible improvement in the emergence of object permanence in these infants after swim training.…”
Section: Introductionmentioning
confidence: 99%